Behavioral pilot study in Panthera onca - Chavarro-Tulcán, Ginette Isabel; Rojas-Rodríguez, Adriana Patricia (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This paper determinate the behavioral responses to an environmental enrichment plan in jaguars, and the variations in the levels of glucocorticoid metabolites. We monitored the behavior of two jaguar females in the Bioparque Los Ocarros one hour three times per day, two days per week during a total of four weeks. The goal was to identify behavioral differences in the jaguars with and without the enrichment plan. In addition, we took fecal samples the days after monitoring and stored them at a -20 °C until their analysis with ELISA test. The enrichment increased de natural behavior in number and frequency and decrease the presentation of stereotypes for one of the females. No significant variation in the levels of glucocorticoid metabolites was observed. Enrichment increases the activity in individuals, but a variation in the levels of glucocorticoid metabolites was not found. We suggest to increase the sampling time in future studies.